Chemical routes to surface enhanced infrared absorption (SEIRA) substrates - Stanglmair, Christoph; Neubrech, Frank; Pacholski, Claudia (Zeitschrift für physikalische Chemie, 2018)
Bottom-up strategies for fabricating SEIRA substrates are presented. For this purpose, wet-chemically prepared gold nanoparticles are coated with a polystyrene shell and subsequently self-assembled into different nanostructures such as quasi-hexagonally ordered gold nanoparticle monolayers, double layers, and honeycomb structures. Furthermore elongated gold nanostructures are obtained by sintering of gold nanoparticle double layers. The optical properties of these different gold nanostructures are directly connected to their morphology and geometrical arrangement - leading to surface plasmon resonances from the visible to the infrared wavelength range. Finally, SEIRA enhancement factors are determined. Gold nanoparticle double layers show the best performance as SEIRA substrates.